Pengenalan Balanced Scored sebagai Organisasi Bisnis - Lafifah Ulfah Dalimunthe; Najwa Khalilah Harahap; Dini Vientiany (Jurnal Bintang Pendidikan Indonesia, 2024)
Performance measurement is an essential thing for a company. To become the winner in this global competition world, the company has to show a performance improvement from period to period. Recently, financial performance measurement is not enough to reflect the real business performance. That why Kaplan developed Balanced Scorecard Concept. The Balanced Scorecard Concept measure the organization’s performance through four perspectives that are the financial perspective, customer perspective, internal business process perspective and learning and growth perspective. In dead, the Balanced Scorecard Concept is a concept in translating strategy into action to achieve organization’s gool in the long term. The action is measured and controlled continually. This article count on the implementation of the Balanced Scorecard Concept in some companies in USA. Many problems a difficulties which occur on the implementation of the concept could became opinion and suggestions for some companies who want to implement the Balanced Scorecard. However, Balanced Scorecard will help organizations (companies) to measure their performance more comprehensive and accurate.